PERAN MOTIVASI KERJA SEBAGAI MEDIASI PENGARUH JOB INVOLVEMENT DAN SELF EFFICACY PADA KINERJA PEGAWAI DINAS SOSIAL KABUPATEN BANGKALAN - Iva Muvida; Fauzan Almanshur (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
A good HR management system is needed to help smooth the operational activities of the organization. Good human resource management can mobilize and manage the workforce so that they are able to carry out predetermined directions. Performance measurement is needed because it will benefit many parties and become a benchmark for evaluating employee performance. To achieve maximum results, of course, the organization will require the application of attitudes of job involvement and self-efficacy in the organization when working. The purpose of this study was to determine the effect of job involvement and self-efficacy on performance through motivation as a mediation. This research method uses quantitative methods. Statistical procedures for data analysis. The measuring instrument in this research is a questionnaire. The sample used in this study were 81 employees. This research was conducted at the Social Service Office of Bangkalan Regency. This study describes instrument test tools (validity and reliability), classical assumption test (normality and linearity), path analysis, hypothesis testing (t test and Sobel). The results of the study showed that there was a significant relationship between job involvement and self-efficacy variables on performance with motivation as a mediation.